2019
DOI: 10.1155/2019/2615154
|View full text |Cite
|
Sign up to set email alerts
|

A Metaheuristic Algorithm to Transporter Scheduling for Assembly Blocks in a Shipyard considering Precedence and Cooperating Constraints

Abstract: Special vehicles named flat transporters are used to deliver heavy ship assembly blocks in shipyards. Because each movement of assembly blocks among workshops needs transporters and the transportations are time-consuming, the scheduling of transporters is important for maintaining the overall production schedule of assembly blocks. This paper considers an optimization transporter scheduling problem for assembly blocks. The objective is to minimize logistics time, which includes empty travel time of transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…To validate the implementation of TS and CS methods, the results were compared with the authors' works [32,39]. The adjustment of the TS and CS parameters improved convergence and achieved better results compared with the GAMS algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the implementation of TS and CS methods, the results were compared with the authors' works [32,39]. The adjustment of the TS and CS parameters improved convergence and achieved better results compared with the GAMS algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results showed that the ant colony optimization algorithm is capable of finding high-quality solutions. Furthermore, Tao et al [32] proposed a metaheuristic based on the hybrid topological graph, genetic algorithm, and TS to minimize travel and waiting times. The algorithm considers time windows, load capacity, and the origin of tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ship segment stacking is different from the production scheduling problem of general products which has the characteristics of complex structure, small production batch, large volume and weight, and inconvenient to transport frequently. Therefore, there are strict spatiotemporal constraints in the production process, which means that it not only needs to satisfy the order in time but also the constraints on space resources [3,4] . Shipbuilding belongs to the One-of-a-Kind Production (OKP) mode, which is also a typical Make-to-Order production mode [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al 11 consider an optimization transporter scheduling problem for assembly blocks; a metaheuristic algorithm is proposed based on the hybrid topological graph and genetic algorithm and tabu search. The experimental results show the efficiency and effectiveness of the proposed algorithm.…”
mentioning
confidence: 99%